Optic neuropathy as the first sign of central nervous system relapse in acute myeloid leukaemia: MRI findings and its diagnostic challenge. Issue 6 (20th June 2019) - Cheung, Michelle; Fang, Benjamin; Lee, Raymand
Abstract : We describe the case of a 22-year-old man who presented with right eye visual impairment and oral mucositis. MRI revealed findings compatible with right optic neuritis. Herpes simplex virus 1 was detected in oral swab. He has a previous history of acute myeloid leukaemia (AML) and was in clinical remission. Initial investigations for possible relapse of AML with central nervous system (CNS) involvement were negative. Treatment for HSV-related optic neuritis was initiated but the patient's vision deteriorated. Repeat MRI revealed right optic nerve infarct, new left optic nerve abnormality and new leptomeningeal enhancement in the brain. Repeated cerebrospinal fluid analysis confirmed CNS relapse of AML. Despite prompt initiation of pulse steroid and high dose intrathecal cytarabine followed by cranial irradiation, the patient never regained his vision. We present a case of unexpected optic neuropathy as first and sole presentation of CNS relapse of AML.